Ricardo Palma and the black problematic - Castillo Sánchez, Wellington (2019)
Within a set of literary values which have been agreed, this re-vision displays the high trait of liminality that defines the Tradition The king of the camanejos, not only in the relationship established between its sources, an oil painting and the oral tradition that explains it, but also in the richness of the concept developed by Arnold Van Gennep, Víctor Turner and Teresa del Valle, from the symbiosis and virtuality of the historical world and the literary world that structure the text. It is done by applying the complexity method to literature, being supported also in the idea of a comprehensive and rigorous study that allows to put into effect the categories of intra, inter and extratextuality. The result is a broad, comprehensive and prolificoutlook towards the elements the Master used to write his work.